2001
DOI: 10.1073/pnas.141218898
|View full text |Cite
|
Sign up to set email alerts
|

How αβ T cells deal with induced TCRα ablation

Abstract: On deletion of the gene encoding the constant region of the T cell antigen receptor (TCR)␣ chain in mature T cells by induced Cremediated recombination, the cells lose most of their TCR from the cell surface within 7-10 days, but minute amounts of surfacebound TCR␤ chains are retained for long periods of time. In a situation in which cellular influx from the thymus is blocked, TCR-deficient naïve T cells decay over time, the decay rates being faster for CD8 ؉ cells (t1/2 Ϸ 16 days) than for CD4 ؉ cells (t1/2 Ϸ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
197
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(208 citation statements)
references
References 36 publications
9
197
1
1
Order By: Relevance
“…This implies, with respect to the reported kinetics of BFL1/A1 expression with return to basal levels at about 48 h after TCR stimulation [22], that at least a fraction of the CD31 -central naive T cells have recently been stimulated via their TCR. The observation that in all samples analyzed BFL-1/A1 expression was not enhanced in CD45RO + memory as compared to CD31 -central naive CD4 + T cells is consistent with the observation that memory CD4 + T cell maintenance is independent of MHC-II [28][29][30][31]. On the other hand the inconsistent up- regulation of BFL-1/A1 in memory as compared to CD31 + thymic naive CD4 + T cells could easily be explained by varying numbers of cells that have recently been activated in the course of foreign antigen encounter.…”
Section: Discussionsupporting
confidence: 89%
“…This implies, with respect to the reported kinetics of BFL1/A1 expression with return to basal levels at about 48 h after TCR stimulation [22], that at least a fraction of the CD31 -central naive T cells have recently been stimulated via their TCR. The observation that in all samples analyzed BFL-1/A1 expression was not enhanced in CD45RO + memory as compared to CD31 -central naive CD4 + T cells is consistent with the observation that memory CD4 + T cell maintenance is independent of MHC-II [28][29][30][31]. On the other hand the inconsistent up- regulation of BFL-1/A1 in memory as compared to CD31 + thymic naive CD4 + T cells could easily be explained by varying numbers of cells that have recently been activated in the course of foreign antigen encounter.…”
Section: Discussionsupporting
confidence: 89%
“…IL-7 is arguably the most important cytokine for T-cell survival. In the present study, we found that F5 T cells have a half life of only 14 days in vivo in the absence of continued IL-7Ra expression, which is shorter than is observed in the absence of TCR signalling [33][34][35]. Interestingly, we found that F5 TCR transgenic T cells exhibited highly distinct survival profiles depending on the host environment they came from.…”
Section: Il-7 Signalling In Vivo Regulates Mitochondrial Homeostasismentioning
confidence: 40%
“…For CD8 + memory T cells, the situation is less clear. Their numbers decline upon ablation of their TCR 98. CD8 + memory T cells not expressing CD122 do, but CD122 expressing cells do not require MHC class I 100, 101, 102.…”
Section: The Lifestyle Of Circulating Memory T Lymphocytesmentioning
confidence: 99%